2012
DOI: 10.2460/javma.240.5.570
|View full text |Cite
|
Sign up to set email alerts
|

Associations among weight loss, stress, and upper respiratory tract infection in shelter cats

Abstract: Results indicated that cats admitted to an animal shelter were likely to lose weight while in the shelter and likely to develop URI, and that cats that had high stress scores were more likely to develop URI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 21 publications
(35 reference statements)
3
123
2
Order By: Relevance
“…Often the assessment of the Stress Score coincided with the long periods of relaxation. This tool have been used in many studies when assessing stress in cats Turner, 1997, 1999b;Ottway and Hawkins, 2003;McCobb et al, 2005;Dybdall et al, 2007;Kry and Casey, 2007;Gooding et al, 2012;Tanaka et al, 2012;Broadley et al, 2013;Moore and Bain, 2013;Rehnberg et al, 2015). It can be difficult to compare the results from different studies using the tool since the calculations from scores differ between studies.…”
Section: Discussionmentioning
confidence: 97%
“…Often the assessment of the Stress Score coincided with the long periods of relaxation. This tool have been used in many studies when assessing stress in cats Turner, 1997, 1999b;Ottway and Hawkins, 2003;McCobb et al, 2005;Dybdall et al, 2007;Kry and Casey, 2007;Gooding et al, 2012;Tanaka et al, 2012;Broadley et al, 2013;Moore and Bain, 2013;Rehnberg et al, 2015). It can be difficult to compare the results from different studies using the tool since the calculations from scores differ between studies.…”
Section: Discussionmentioning
confidence: 97%
“…32,33 Cats faced with unexpected changes to their management may decrease appetite and water intake, avoid elimination for 24 hours (potentially increasing the risk of constipation), and defecate outside the litter tray. 34 In general, food intake and stress seem to be negatively correlated in cats, 28 whereas in dogs, associations have been made between increased stress and coprophagia 35 and inflammatory bowel disease. 36 The Integument…”
Section: Reproductive Systemmentioning
confidence: 98%
“…26,27 In catteries, it has been found that cats exhibiting high levels of stress are about 5 times more likely to develop upper respiratory tract infection compared with cats exhibiting lower levels. 28 Stress during pregnancy in both human and nonhuman animals can also reduce immunocompetence in the offspring. 29,30 Gastrointestinal System…”
Section: Reproductive Systemmentioning
confidence: 99%
“…Several diseases as well as unwanted feline behaviors have been associated with stressful environmental situations. [1][2][3] Providing an appropriate environment for feline patients in their home and at the veterinary practice can prevent, improve or resolve these problems. 4,5 The terms environmental enrichment and environmental modifications have been used extensively in the literature to refer to environmental changes for the benefit of the cat.…”
Section: Why Environmental Needs?mentioning
confidence: 99%